Asociación de las características oclusales con la edad y género en niños con dentición decidua de una institución educativa pública del distrito de Ate Vitarte en el año 2013 - Flores Bazán, Andrea Alejandra (2014)
Objective: To determine the association of features occlusal with age and gender in children with deciduous dentition of a public educational institution in the district of Ate Vitarte in 2013. Methods: The sample was conformed by 108 children with complete deciduous dentition between 3 and 5 years of the IE Amauta No. 1285-216 located in Ate Vitarte in 2013. All variables were recorded on the data collection form, these were, type of arch, primate spaces, palatine hall relation of molars, bilateral terminal molar relation, bilateral canine relationship, curve of Spee, midline, overjet and overbite. In addition to the age and gender of the scholar. Frequencies were obtained and the chi square test were conducted to determine associations between variables. Results:. Only found statistically significant association between superior primates spaces (p=0.041) and inferior (0.002), bilateral terminal molar relation (p=0.040), lower midline (p=0.032) and age. Conclusions: In this study, was found that most of the children presented normal occlusal characteristics. No association of most occlusal characteristics were found with age and gender.